A joint optimal dispatching method of wind-solar-hydro generation system. Issue 3 (February 2019) - Chen, Siyu; Fang, Guohua; Huang, Xianfeng; Yan, Min
Abstract: As the first choices among new energy resources to alleviate the crisis of fossil fuels and solve the problem of environmental pollution, wind and solar power generation have attracted more and more attention. However, the instability and intermittency of its output have become the bottleneck restricting its large-scale development. In the system with wind and PV power, conventional energy is often required to reduce the volatility of the output. Due to the characteristics of stable output and quick response to load change, the cascade hydropower station compensates the instability of wind and solar power output. In this paper, a combined generation model including wind power, photovoltaic generation and the cascade hydropower stations has been built and NSGA-II has been used to work out a scheduling scheme, which has been proved to perform better than other algorithms.